Genomic Diversity of the Ostreid Herpesvirus Type 1 Across Time and Location and Among Host Species - Morga, Benjamin; Jacquot, Maude; Pelletier, Camille; Chevignon, Germain; Dégremont, Lionel; Biétry, Antoine; Pepin, Jean-François; Heurtebise, Serge; Escoubas, Jean-Michel; Bean, Tim P.; Rosani, Umberto; Bai, Chang-Ming; et al. (Frontiers in Microbiology, 2021)
The mechanisms underlying virus emergence are rarely well understood, making the appearance of outbreaks largely unpredictable. This is particularly true for pathogens with low per-site mutation rates, such as DNA viruses, that do not exhibit a large amount of evolutionary change among genetic sequences sampled at different time points. However, whole-genome sequencing can reveal the accumulation of novel genetic variation between samples, promising to render most, if not all, microbial pathogens measurably evolving and suitable for analytical techniques derived from population genetic theory. Here, we aim to assess the measurability of evolution on epidemiological time scales of the Ostreid herpesvirus 1 (OsHV-1), a double stranded DNA virus of which a new variant, OsHV-1 μVar, emerged in France in 2008, spreading across Europe and causing dramatic economic and ecological damage. We performed phylogenetic analyses of heterochronous (n = 21) OsHV-1 genomes sampled worldwide. Results show sufficient temporal signal in the viral sequences to proceed with phylogenetic molecular clock analyses and they indicate that the genetic diversity seen in these OsHV-1 isolates has arisen within the past three decades. OsHV-1 samples from France and New Zealand did not cluster together suggesting a spatial structuration of the viral populations. The genome-wide study of simple and complex polymorphisms shows that specific genomic regions are deleted in several isolates or accumulate a high number of substitutions. These contrasting and non-random patterns of polymorphism suggest that some genomic regions are affected by strong selective pressures. Interestingly, we also found variant genotypes within all infected individuals. Altogether, these results provide baseline evidence that whole genome sequencing could be used to study population dynamic processes of OsHV-1, and more broadly herpesviruses.